KESETIMBANGAN ADSORPSI ISOTERMIS LOGAM FE (II) PADA ARANG TONGKOL JAGUNG - Saripah Sobah; Adam Adam; Joko Triyatno; Yano Hurung Anoi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The purpose of this study was to determine the optimum absorption time of corn cob charcoal in absorbing Fe (II) ions, and the effect of pH of the solution on Fe concentration was absorbed in batch isothermic conditions using the Langmuir equation. The study was carried out under atmospheric conditions, temperature 27oC. A total of 0.6 g of char is added to 50 ml of Fe solution with various concentrations and then stirred using a magnetic stirrer at a speed of 150 rpm. Equilibrium data is taken after the process last for 24 hours, while to determine the contact time is selected at 5, 10, 15, 20, and 25 minutes. The optimum absorption time of corn cob charcoal in absorbing Fe (II) ions is 20 minutes. The amount of Fe absorbed increases with increasing pH.